Computing Capabilities of Crystals - Demidov, Aleksey A. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The work is devoted to investigation from the standpoint of quantum physics the possibility of using the scattering of a beam of light on crystals for calculations. There is proposed a model of computation, corresponding the transformation of the light beam as it passes through the crystal, and provided the necessary formulas for the calculation of the model. It is necessary to emphasize the abstract nature of the research, which is aimed at creation of the theoretical basis for further study of the produced algebraic structures, rather than the construction of a real device – a quantum computer or the like. The work carried out by the program of creation of algebraic computer.